Sexual and reproductive health issues of women attending psychiatric clinic in India-A qualitative study - Sundaram Vijayalakshmi; Kaipangala Rajagopal; Radhakrishnan Govindan; Sundarnag Ganjekar; P V Prathyusha; Leena K Chacko (Wolters Kluwer Medknow Publications, 2024)
Background: Women with mental illness (WMI) experience considerable disparities in sexual and reproductive health (SRH) when compared to the general population. Due to their restricted access to SRH services, they have unmet contraceptive needs, a greater prevalence of sexually transmitted infections (STIs), and sexual dysfunction. The study aimed to explore the SRH issues of WMI in a tertiary care psychiatric outpatient clinic in Bengaluru, India. Materials and Method: A qualitative hermeneutic phenomenological approach was used. A reproductive age group (18-49 years) WMI (n = 32) was selected by purposive sampling technique. The period of data collection was from January 2021 to September 2021. An in-depth face-to-face interview was conducted using a validated interview schedule. Hycner's explicitation process was used to investigate the constituents of a phenomenon. Result: The codes revealed potential themes and subthemes. SRH issues faced by WMI were organized under three main themes, namely, (1) factors responsible for sexual dysfunction, (2) symptoms of STI and treatment adherence, and (3) use of contraception and its barrier. Conclusions: Sexual dysfunction among WMI is contributed by numerous factors. Women were exhibited limited knowledge of STI symptoms and treatment compliance. Such women experience issues with current method of contraception and are unaware of the alternatives. The findings of this study may be helpful for clinical nurses in drawing attention to and increasing knowledge of the reproductive health issues that women with psychiatric disorders face, taking the required precautions, and devising strategies for minimizing harm.